2017
DOI: 10.1111/bjd.15552
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of histological regression in primary cutaneous melanoma: a systematic review and meta-analysis

Abstract: Summary The prognostic significance of histological regression in primary melanoma has been debated for many years. We aim to review the evidence to see how histological regression may affect prognosis. A systematic review was performed by searching in MEDLINE, Scopus and the Cochrane Library from 1 January 1966 to 1 August 2015. All studies reporting hazard ratios or data on survival and histological regression were included. Primary random‐effects meta‐analyses were used to summarize outcome measures. Hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…Another tumour characteristic of interest is regression. Regression has been found to be an independent prognostic factor for patients with melanoma in general. In line with previous studies, independent prognostic value was not proven for SN‐negative melanoma in the present analysis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another tumour characteristic of interest is regression. Regression has been found to be an independent prognostic factor for patients with melanoma in general. In line with previous studies, independent prognostic value was not proven for SN‐negative melanoma in the present analysis.…”
Section: Discussionsupporting
confidence: 82%
“…The AJCC acceptance criteria for individualized prognostic models were taken into account when building the model. The following potential prognostic factors were selected based on clinical experience and literature review: sex, age, ulceration, Breslow thickness, primary tumour site, melanoma subtype, Clark level, tumour mitotic rate, regression, number of SN fields and total number of SNs. To address the possibility of a non‐linear association with outcomes, the continuous variables age and Breslow thickness were modelled by logarithmic transformation.…”
Section: Methodsmentioning
confidence: 99%
“…Although the lymphocytic infiltrate has been described as a favourable prognostic feature, 18 complete agreement on the role of histological regression has not been reached to date; indeed, either a negative or protective role on prognosis has been attributed to regression. [4][5][6]19 Moreover, it has been suggested that early immune activation could explain the different immunotherapy response rates in clinical practice. 20 After revision of slides and evaluation of the extent of regression, we identified a quantitative cut-off value (10%) of histological regression associated with a different outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma is one of the most immunogenic tumours. Regression has been speculated to be a possible marker of immunogenic systemic response of this survival advantage [37] . Some authors [38,39] showed that the presence of regression in the primary tumour results from a T-cell immune response associated with a decreased risk of nodal progression.…”
mentioning
confidence: 99%